2016
DOI: 10.1590/s1677-5538.ibju.2014.0607
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sepsis following transrectal ultrasound guided prostate biopsy at a tertiary-care medical center in Lebanon

Abstract: Background Urosepsis is a rare but life-threatening complication following transrectal ultrasound (TRUS) guided needle prostate biopsy. Despite the technological and pharmacological improvements, the problem of bacterial urosepsis after prostate biopsy remains. A strategy for preventing urosepsis following TRUS prostate biopsy in areas with high prevalence of resistant strains or patients presenting risk factors is lacking.Objectives The aim of this study was to assess the prevalence of urosepsis, as well its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Therefore, the hospitalization rate of the patients in the TP group (0%) was obviously lower than that in the TR group (7.4%) (Table 2). In addition, median (25–75% quartiles) of VAS scores of the patients in the TP and TR groups was 3 [3, 4] and 4 [35], respectively, but there was no statistically significant difference between these two groups ( p = 0.085 ) (Table 3) (Fig. 6).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the hospitalization rate of the patients in the TP group (0%) was obviously lower than that in the TR group (7.4%) (Table 2). In addition, median (25–75% quartiles) of VAS scores of the patients in the TP and TR groups was 3 [3, 4] and 4 [35], respectively, but there was no statistically significant difference between these two groups ( p = 0.085 ) (Table 3) (Fig. 6).…”
Section: Resultsmentioning
confidence: 96%
“…hematuria, hematospermia, rectal bleeding, and acute urine retention) to severe complications (e.g. anemia and syncope) [3]. Approximately 4 to 5% of the patients who undergo this procedure require hospital admission due to infection-related complications (ranging from bacteriuria to sepsis) [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some studies indicate that age, BMI ≥ 25 kg/m 2 , diabetes mellitus, preoperative catheter, prostate volume, multiple punctures, history of hypertension, history of antiplatelet drugs, preoperative antibiotics and clean perfusion are risk factors for infection after TRUS-Bx. 12 , 21 25 However, some other scholars suggest that age, prostate volume, history of hypertension, PSA, fPSA/PSA, history of antiplatelet drugs, history of coronary heart disease and pathological results are not risk factors of infection after TURS-PB. 11 , 23 In this study, we found that age, hypertension, indwelling catheter, prostate volume, PSA, fPSA/PSA, pathological type and antibiotic use history were not independent risk factors of SIRS after TRUS-Bx.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study of 265 patients, the prevalence of sepsis was found to be 9.4% [5]. Antibiotic prophylaxis minimizes life-threaten ing septic complications [5]. However, septic complica tions cannot be avoided completely.…”
Section: Introductionmentioning
confidence: 99%